A Multi-Dimensional Comparative Assessment Methodology for Policy Analysis: A Multi-Country Study of the Agricultural Sector - Peter Nijkamp; Gabriella Vindigni (Tinbergen Institute, 1999)
This paper offers an overview of assessment methods for physicalplanning, with a particular focus on the agricultural sector. Anattempt is made to link multi-criteria analysis to meta-analysis byapplying rough set theory as a framework for comparative study. Anempirical application on the explanation of productivity differencesin OECD countries is used to ilustrate the potential of thisapproach.
Keywords: 330; Agrarpolitik; Vergleich; Bewertung; OECD-Staaten